Introduction of a new key step in lateral approach thyroidectomy: a randomised prospective study on thirty patients - Phookan, Jyotirmoy; Gupta, Shilpi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The school of Bilroth in Vienna started modern thyroid surgeries in 1860s.1 Thyroidectomy was associated with high mortality, recurrent laryngeal nerve injuries and tetany. One and a half century down the timeline, complications still occur. Although, in experienced hands, the thyroid surgeries performed today are associated with minimal mortality and morbidity. Lateral approach thyroidectomy is a commonly practiced approach with fewer complications. We carried out a study to assess the efficacy, safety and advantages of lateral approach thyroidectomy with a new key step. Methods: A prospective study was performed on thirty patients undergoing conventional open thyroidectomy from January to July 2019 at a tertiary care hospital in north east India. All patients underwent open thyroidectomy via lateral approach in which identifying superior belly of omohyoid was considered a key step of surgery. Basic demographic data, preoperative diagnosis, operative time, blood loss, need for transection of strap muscles and complications were recorded. Results: There were no intra-operative complications, without the need to cut strap muscles or sacrifice superior belly of omohyoid in any case. Voice change was seen in one case, improved after steroid administration. One case developed tetany after total thyroidectomy managed with calcium supplements. Conclusions: Results suggested that lateral approach of thyroidectomy is a quick and safe technique where identification of superior belly of omohyoid considered as our key step, enabled easy delivery of superior pole of thyroid and facilitates easy identification and preservation of vital structures; thus, causing least morbid sequelae.